(untitled) (Revista Brasileira de Ensino de Ciências e Matemática, 2025)
The interdisciplinary teaching represents an important tool for meaningful learning in Mathematics, with a view to contextualizing and applying concepts in other areas of knowledge. In this context, official educational regulations in Brazil in the area of Mathematics and its Technologies defend the construction of a more integrated vision of Mathematics and its relationship with the Science. Among the skills highlighted for the teaching of Mathematics in Basic Education, the interpretation of phenomena and the solution of problem situations based on concepts of regular polyhedra stand out. Although the importance of this topic for improving the teaching and learning of Mathematics is known, the applications of regular polyhedra are still little explored in the school environment and even in literature. In this sense, this work presents a literature review, of an exploratory-descriptive nature, with the aim of highlighting regular polyhedra in the modeling of phenomena in scientific and technological areas for use of this relationship in the educational environment. The results showed that the geometric elements and properties of regular polyhedra are used to model phenomena in areas of basic science (biology, chemistry and materials) and applied science (robotics, cartography, meteorology and mineralogy), meaning an alternative approach to the improvement of the Mathematics and Technologies teaching in secondary school.